If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(f-9)=18
We move all terms to the left:
3(f-9)-(18)=0
We multiply parentheses
3f-27-18=0
We add all the numbers together, and all the variables
3f-45=0
We move all terms containing f to the left, all other terms to the right
3f=45
f=45/3
f=15
| 6+p=–6(–2p+10) | | m/6=(m+3)/10 | | 1-100x2=0 | | -12.8=y-16.4 | | 4.2-2=0.5(8.4x+6) | | −6=2(w+5) | | 5(2c+1)-(c+2)=-43 | | 3x+2(-x+3)=9 | | 1.5x+4=2x+24 | | -3y^2+18y-27=0 | | 144x-60=12(12x-5) | | 0.2x-3.2/5=18 | | 21÷10n=11÷6 | | -106+x=89-12x | | 10x+26x-7=9(4x+7) | | 5-p/3=4 | | 5x+12=x^2+4x | | 7.6×p=54* | | x(2x-3)=-4x | | 19c+26c=41+14c | | 29x+3=29x+69 | | 9x+15=16x+15 | | 0=x^2-x-132 | | 3y+3=3y-8 | | 5x+23x-9=7(4x+4) | | -5w+5=5w-75 | | 4x=8(3) | | 3(3x+2)-2=7x+6 | | x-188=15x+106 | | -1.4(3x-4)=-4.2x+31 | | 14-2y-3y=-11 | | 2p+3p=-14+34 |